2005
DOI: 10.1111/j.1464-5491.2005.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine improves insulin sensitivity without alteration of serum adiponectin in obese subjects with Type 2 diabetes

Abstract: We conclude that treatment with sibutramine 15 mg once daily effectively reduces weight and enhances insulin sensitivity without alteration of serum adiponectin levels in obese patients with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…However, Abbasi et al (46) showed that there were no alteration in serum adiponectin concentrations with significant improvement in insulin resistance after sibutramine treatment in insulin-resistant obese non-diabetic patients. Likewise, Hung et al (28) demonstrated that sibutramine treatment effectively reduced weight and enhanced insulin sensitivity without an alteration in serum adiponectin concentrations in obese type 2 diabetic patients. In other study, Tambascia et al (15) suggested that 6 months sibutramine treatment was effective in improving of HOMA-IR with no change in fibrinogen levels in the non-diabetic women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Abbasi et al (46) showed that there were no alteration in serum adiponectin concentrations with significant improvement in insulin resistance after sibutramine treatment in insulin-resistant obese non-diabetic patients. Likewise, Hung et al (28) demonstrated that sibutramine treatment effectively reduced weight and enhanced insulin sensitivity without an alteration in serum adiponectin concentrations in obese type 2 diabetic patients. In other study, Tambascia et al (15) suggested that 6 months sibutramine treatment was effective in improving of HOMA-IR with no change in fibrinogen levels in the non-diabetic women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies showed that adiponectin levels changed with weight loss (26,27). However, in a recent study, treatment with sibutramine 15 mg once daily effectively reduced weight and enhanced insulin sensitivity without alteration of serum adiponectin levels in obese patients with type 2 diabetes (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[76][77][78][79] Sibutramine reduced high sensitivity C-reactive protein (hsCRP) levels in some studies 80,81 but not in others. 82 Sibutramine along with diet and exercise reduced the serum levels of the pro-inflammatory cytokines tumor necrosis factor α (TNFα) and interleukin 6 (IL-6) and increased the serum levels of the anti-inflammatory cytokine IL-10. 83 These anti-inflammatory effects were independent of weight loss in some studies 80 but were related to weight loss in others.…”
Section: Sibutramine and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…In one study, adiponectin levels remained unchanged by treatment with sibutramine even though modest weight loss was achieved; however, another study observed increases in adiponectin levels. 62,63 Common side effects include an increase in blood pressure and pulse rate, 59 therefore it should be used with care in patients with high blood pressure.…”
Section: Therapies For Weight Lossmentioning
confidence: 99%